Accurate initiation at RNA polymerase II promoters in extracts from Saccharomyces cerevisiae. - Lue, N F (1987)
A yeast nuclear extract supported transcription from the CYC1 and PYK1 promoters. Transcription was initiated in vitro at or near sites used in vivo. Deletion of "TATA" sequences abolished the reaction. alpha-Amanitin (10 micrograms/ml) and chloride (100 mM) were highly inhibitory.